Impact ionisation mass spectrometry of platinum-coated olivine and magnesite-dominated cosmic dust analogues - Hillier, Jon; Trieloff, Mario; Guglielmino, Massimo; Postberg, Frank (Planetary and space science, 2018)
Impact ionisation mass spectrometry enables the composition of cosmic dust grains to be determined in situ by spacecraft-based instrumentation. The proportion of molecular ions in the impact plasma is a function of the impact velocity, making laboratory calibration vital for the interpretation of the mass spectra, particularly at the low velocities typical of lunar or asteroid encounters. Here we present an analysis of laboratory impact ionisation mass spectra from primarily low (<15 km s−1) velocity impacts of both olivine and magnesite-dominated particles onto the SUrface Dust Mass Analyzer (SUDA) laboratory mass spectrometer. The cation mass spectra show characteristic peaks due to their constituent elements, with Mg, Al, Si, C, Ca, O and Fe frequently present. Contaminant species from the conductive coating process (B, Na, K, C, Pt) also occur, at varying frequencies. Possible saponite or talc inclusions in the magnesite particles are revealed by the presence of Si, Fe, Ca and Al in the magnesite mass spectra. Magnesium is clearly present at the lowest impact velocities (3 km s−1), at which alkali metals were presumed to dominate. Peaks attributed to very minor amounts of water or hydroxyl present in the grains are also seen at low velocities in both cation and anion mass spectra, demonstrating the feasibility of impact ionisation mass spectrometry in identifying hydrated or hydrous minerals, during very low velocity encounters or with very low abundances of water or hydroxy groups, in the impinging grains. Velocity thresholds for the reliable identification of the major elements within the magnesite and olivine cation spectra are presented. Additionally, relative sensitivity factors for Mg (5.1), Fe (1.5) and O (0.6) with respect to Si, in the olivine particles, at impact speeds >19 km s−1, were found to be very similar to those previously determined for orthopyroxene-dominated particles, despite different target and projectile materials. This confirms that quantitative analyses of mineral dust grain composition in space is viable despite initially poorly-constrained mineralogy.
Available online: 12 October 2017
Gesehen am 29.08.2019